Comparative effectiveness of clozapine and non-clozapine atypical antipsychotics provided by the Brazilian National Health System in adults with schizophrenia - Vieira, Júlio César Menezes; Reis, Edna Afonso; Guerra, Augusto Afonso; Oliveira, Helian Nunes de; Ruas, Cristina Mariano (Frontiers in Psychiatry, 2024)
Introduction: Currently, 21 million people live with the disease, mostly in low to middle-income countries. We aimed to assess the survival of patients with schizophrenia using clozapine compared with non-clozapine atypical antipsychotics provided by the Brazilian National Health System using real-world data.Materials and methods: This is an open retrospective cohort study of patients diagnosed with schizophrenia to whom atypical antipsychotics were dispensed by the Brazilian National Health System between 2000 and 2015, based on deterministic-probabilistic pairing of administrative data records. The Kaplan-Meier method was used to estimate the cumulative probability of survival and the Cox proportional hazards model was adjusted to assess the risk factors for survival via the hazard ratio (HR).Result: Participants were 375,352 adults with schizophrenia, with an overall survival rate of 76.0% (95%CI 75.0-76.0) at the end of the cohort. Multivariate analysis indicated a greater risk of death for men (HR=1.30; 95%CI 1.27-1.32), older adults (HR=17.05; 95%CI 16.52-17.60), and in the Southeast region of Brazil (HR=1.20; 95%CI 1.17-1.23). Patients who used non-clozapine atypical antipsychotics had a 21% greater risk of death when compared to those taking clozapine (HR=1.21; 95%CI 1.14-1.29). Additionally, a history of hospitalization for pneumonia (HR=2.17; 95%CI 2.11-2.23) was the main clinical variable associated with increased risk of death, followed by hospitalization for lung cancer (HR=1.82; 95%CI 1.58-2.08), cardiovascular diseases (HR=1.44; 95%CI 1.40-1.49) and any type of neoplasia (HR=1.29;.Discussion: This is the first published Brazilian cohort study that evaluated survival in people with schizophrenia, highlighting the impact of atypical antipsychotics. In this real-world analysis, the use of clozapine had a protective effect on survival when compared to olanzapine, risperidone, quetiapine, and ziprasidone.